Clinical experience with near-infrared ray catheter, a fluorescent ureteral catheter, on laparoscopic surgery for colon diverticulitis: A case report. Issue 21 (28th May 2021) - Osumi, Wataru; Yamamoto, Masashi; Taniguchi, Kohei; Masubuchi, Shinsuke; Hamamoto, Hiroki; Ishi, Masatsugu; Izuhara, Keisuke; Tanaka, Keitaro; Okuda, Junji; Uchiyama, Kazuhisa
Abstract: Rationale: As the world's population ages, the number of surgical cases of colovesical fistulas secondary to colon diverticulitis is also expected to increase. The key issue while performing laparoscopic surgery for these fistulas is the avoidance of iatrogenic ureteral injury. There are no reports of Near-infrared Ray Catheter being used in surgery for diverticulitis, which is one of the diseases with the highest risk of ureteral injury. We present a case of a male patient with colovesical fistulas secondary to sigmoid colon diverticulitis who underwent laparoscopic surgery with visualization of the ureter using a new surgical technique in laparoscopic surgery. Patient's concern: An 82-year-old man presented to our urological department with general fatigue and air and fecal matter in the urine. Diagnoses: Cystography showed delineation of the sigmoid colon. Abdominal computed tomography findings revealed multiple sigmoid colon diverticula with thickened walls as well as large stones and a small amount of air in the bladder. He was diagnosed with a urinary tract infection with colovesical fistulas and bladder stones due to sigmoid diverticulitis. Interventions: After the creation of a transverse colostomy, we scheduled a laparoscopic anterior resection and cystolith removal. Outcomes: Severe inflammatory adhesions around the sigmoid colon and a high risk of ureteral injury were expected preoperatively. After induction of anesthesia, we inserted a Near-infrared Ray Catheter, a fluorescent ureteral catheter, which allowed us to easily identify and visualize the ureter in real-time. This allowed bowel dissection without concerns of ureteral injury. The operative time for the gastrointestinal part of the procedure was 150 minutes, and the patient was in a good general condition after the operation and was discharged on postoperative day 7. Lessons: The course of the ureter was easily and quickly identified by the green fluorescence from the ureteral catheter during laparoscopic surgery for fistulas associated with diverticulitis, where severe inflammation and dense fibrosis were present. Our technique is an easy and feasible approach that provides real-time urethral navigation during surgery for colovesical fistulas secondary to colon diverticulitis.